[Letter to coalition organizations for NYS No-Smoking Bill] (Tufts Archival Research Center, 2007)
Form letter to organizations that filed memorandums against the No-Smoking Bill in 1982, urging them to resubmit for the 1983 session. Lists organizations that have publicly opposed bill, as well as names and addresses of leadership. Cites onerous nature of the legislation, as well as its impracticality and unenforceability.